Exploration of the Structural Space in 4(3H)-Quinazolinone Antibacterials - Qian, Yuanyuan (J Med Chem, 2020)
We report herein the syntheses of 79 derivatives of the 4(3H)-quinazolinones and their structure–activity relationship (SAR) against methicillin-resistant Staphylococcus aureus (MRSA). Twenty one analogs were further evaluated in in vitro assays. Subsequent investigation of the pharmacokinetic properties singled out compound 73 ((E)-3-(5-carboxy-2-fluorophenyl)-2-(4-cyanostyryl)quinazolin-4(3H)-one) for further study. The compound synergized with piperacillin-tazobactam (TZP) both in vitro and in vivo in a clinically relevant mouse model of MRSA infection. The TZP combination lacks activity against MRSA, yet it synergized with compound 73 to kill MRSA in a bactericidal manner. The synergy is rationalized by the ability of the quinazolinones to bind to the allosteric site of penicillin-binding protein (PBP)2a, resulting in opening of the active site, whereby the β-lactam antibiotic now is enabled to bind to the active site in its mechanism of action. The combination effectively treats MRSA infection, for which many antibiotics (including TZP) have faced clinical obsolescence.